Numerical algorithms for personalized search in self-organizing information networks - Kamvar, Sep 1977- (Princeton University Press, 2010)
"This book lays out the theoretical groundwork for personalized search and reputation management, both on the Web and in peer-to-peer and social networks." The book develops scalable algorithms that exploit the graphlike properties underlying personalized search and reputation management, and delves into realistic scenarios regarding web-scale data.--[book cover]